Physical activity based intervention program on health, bone mineral density and fitness status for rheumatology patient over 60 years of age - Kopkáné Plachy Judit; Vécseyné Kovách Magdolna; Ihász Ferenc; Bognár József (Sciendo, 2014)
Study aim: regular physical activity is important both for the prevention of illnesses and for rehabilitation purposes because it has significant impact on the physical and mental health of the elderly. The purpose of this study was to assess whether two different half-year regular training programmes had positive effects on health dimensions, bone mineral density, and fitness status in population of women aged over 60 years.